2011
DOI: 10.1093/nar/gkr747
|View full text |Cite
|
Sign up to set email alerts
|

ATP-regulated interactions between P1 ParA, ParB and non-specific DNA that are stabilized by the plasmid partition site, parS

Abstract: Localization of the P1 plasmid requires two proteins, ParA and ParB, which act on the plasmid partition site, parS. ParB is a site-specific DNA-binding protein and ParA is a Walker-type ATPase with non-specific DNA-binding activity. In vivo ParA binds the bacterial nucleoid and forms dynamic patterns that are governed by the ParB–parS partition complex on the plasmid. How these interactions drive plasmid movement and localization is not well understood. Here we have identified a large protein–DNA complex in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 42 publications
(88 reference statements)
12
45
0
Order By: Relevance
“…The bridging activity of SopA and SopB studied here has features similar to the DNA-bridging complexes described for P1 and pSM19035 of Streptococcus pyogenes (14,24). For all systems, DNA bridging required both proteins and ATP, and bridge disassembly was coupled to ParB-stimulated ATP hydrolysis.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The bridging activity of SopA and SopB studied here has features similar to the DNA-bridging complexes described for P1 and pSM19035 of Streptococcus pyogenes (14,24). For all systems, DNA bridging required both proteins and ATP, and bridge disassembly was coupled to ParB-stimulated ATP hydrolysis.…”
Section: Discussionsupporting
confidence: 63%
“…For all systems, DNA bridging required both proteins and ATP, and bridge disassembly was coupled to ParB-stimulated ATP hydrolysis. For P1, the complex was proposed to bridge plasmid and nucleoid and was referred to as the "nucleoid-adaptor complex" (NAC) (24). For pSM19035, the bridging was proposed to play a role in plasmid pairing as well as in forming an NAC-like complex (14).…”
Section: Discussionmentioning
confidence: 99%
“…The nonhydrolyzable analog ATP␥S supported assembly of larger and more stable complexes than those formed with ATP. From these observations, we concluded that NAC assembly and disassembly required ATP binding and hydrolysis, respectively (26).…”
Section: Parak122r Is Defective In Disassembly Of Nucleoid Adaptor Comentioning
confidence: 93%
“…, NAC-We next tested the ability of ParAK122R to support the formation of NAC, the large ParA-ParB-DNA com- plexes that can be detected in sucrose gradient sedimentation and light scattering assays (26). The sedimentation assay measures the change that protein binding has on the migration of DNA through a sucrose gradient.…”
Section: Parak122r Is Defective In Disassembly Of Nucleoid Adaptor Comentioning
confidence: 99%
See 1 more Smart Citation